Transcranial direct current electrical stimulation in stroke - Almeida, Sara Anne Evangelista de (2024)
Introduction: Cerebral Vascular Accident (CVA) compromises blood circulation in certain areas of the brain, stroke can be characterized as ischemic stroke formed by a clot preventing blood circulation, and hemorrhagic stroke is a rupture of a certain blood vessel. Post-stroke treatments have been evolving in the scientific field, the use of electrical stimulation using direct currents, through clinical results, can accelerate and increase the functional recovery of the affected individual. Objectives: To understand how Transcranial Direct Current Stimulation is used in patients after a stroke, as it is assumed that using the necessary resources to obtain it can achieve efficacy to be na ally in treatment. Methodology: This work consists of a bibliographical review, which seeks to compile and analyze relevant studies on the use of transcranial electrical stimulation in stroke, searching the database in SciELO and DeCS/MeSH Conclusion: tDCS brings a significant improvement in helping the individual in activities of daily life, becoming more capable and functional after the disease, which is one of the main factors that affect their physical, mental and cognitive capacity.